In the shadow of catastrophe : German intellectuals between apocalypse and enlightenment - Rabinbach, Anson (Berkeley : University of California Press, 1997)
These essays by eminent European intellectual and cultural historian Anson Rabinbach address the writings of key figures in twentieth-century German philosophy. Rabinbach explores their ideas in relation to the two world wars and the horrors facing Europe at that time. Analyzing the work of Benjamin and Bloch, he suggests their indebtedness to the traditions of Jewish messianism. In a discussion of Hugo Ball's little-known Critique of the German Intelligentsia, Rabinbach reveals the curious intellectual career of the Dadaist and antiwar activist turned-nationalist and anti-Semite. His examination of Heidegger's "Letter on Humanism" and Jaspers's The Question of German Guilt illuminates the complex and often obscure political referents of these texts. Turning to Horkheimer and Adorno's Dialectic of Enlightenment, Rabinbach offers an arresting new interpretation of this central text of the critical theory of the Frankfurt School. Subtly and persuasively argued, his book will become an indispensable reference point for all concerned with twentieth-century German history and thought.
Frontmatter -- Contents -- Acknowledgments -- Introduction: Apocalypse and Its Shadows -- PART I. WORLD WAR I -- PART II. 1946-1947 -- Conclusion -- Notes -- Index
Includes bibliographical references (pages 209-253) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Germany -- Intellectual life -- 20th century; Germany -- Politics and government -- 1918-1933.; Arts and society -- Germany -- History -- 20th century; Enlightenment -- Germany; Jews -- Germany -- Intellectual life; Allemagne -- Vie intellectuelle -- 20e siècle.; Allemagne -- Politique et gouvernement -- 1918-1933.; Arts et société -- Allemagne -- Histoire -- 20e siècle.; Siècle des Lumières -- Allemagne; Juifs -- Allemagne -- Vie intellectuelle; HISTORY; HISTORY / Europe / General; Arts and society; Enlightenment; Intellectual life; Jews -- Intellectual life; Politics and government; Germany; Filosofen; Joodse vraagstuk; Duitsland; Germany; Regions & Countries - Europe; History & Archaeology; 1900-1999; activism; adorno; anti semitism; anti war; benjamin; bloch; critical theory; critique of the german intelligentsia; dadaism; dialectic of enlightenment; europe; frankfurt school; german history; german philosophy; heidegger; history; horkheimer; hugo ball; interwar period; jasper; jewish intellectuals; jewish messianism; letter on humanism; messiah; messianic; nationalism; nonfiction; philosophy; question of german guilt; social theory; world war one; world war two; ww1.; ww2.; History